Paternalism and factitious disorder: medical treatment in illness deception. Issue 4 (9th June 2015) - Fry, Anthony; Gergel, Tania L.
Abstract: The primary aims are to consider whether a range of paternalistic medical interventions can be justified in the treatment of factitious disorder (FD) and to show that the particularities of FD and its management make it an ideal phenomenon to highlight the difficulties of balancing respect for self‐determination, responsibility and duty of care in psychiatry. FD is usually classified as a mental disorder involving deliberate and hidden feigning or inducement of illness, in order to achieve patient status. Both the nature of the disorder and the approach to treatment are controversial and under‐researched. It is argued that FD should be classified as a mental disorder; may well expose the patient to extreme risk; can warrant paternalistic interventions, in order to fulfil duty of care. Moreover, treatment of FD is inherently paternalistic and therefore raises interesting questions about justifications and type of paternalistic interventions in psychiatry both for FD and in general. A brief account of key questions concerning psychiatry and paternalism is followed by some case histories of FD, the clinical dilemmas posed and the question of how this disorder might warrant paternalistic interventions. In order to answer this question, two things are considered: the legitimacy and character of FD as a mental disorder; possible frameworks for and types of paternalistic interventions. To conclude, it is argued that there are no compelling reasons for rejecting the use of paternalistic interventions for FD, but that further investigation of FD and type and frameworks for psychiatric paternalism, in relation to FD and other mental disorders, are urgently needed.